DESCRIBE KINESTHETIC AND VISUAL LEARNERS AND HOW DO THEY LEARN BEST - Qoʻchqorov Zulfizar Abduxamid Qizi; Sobirova Odina Jaxongirovna (Лучшие интеллектуальные исследования, 2023)
ANNOTATION. The purpose of this research is to analysis the impacts of visual, auditory, kinesthetic learning styles on economics education teaching. One of the most important uses learning styles is that it makes it easy for teachers to incorporate them into their teaching. There are various styles of learning. Three of the most popular are visual, auditory, and kinesthetic, in way students take the information. While students use all of their senses to take the information, they seem to have preferences in how they learn best.